2007
DOI: 10.1007/s10067-007-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

Accurate diagnosis of acute abdomen in FMF and acute appendicitis patients: how can we use procalcitonin?

Abstract: This study was conducted to define the value of procalcitonin (PCT) levels in the differential diagnosis of abdominal familial Mediterranean fever (FMF) attacks from acute appendicitis. From October 2006 to January 2007, 28 FMF (12 males, 16 females) patients with acute abdominal attacks and 34 patients (18 males) with acute abdomen who underwent operation with the clinical diagnosis of acute appendicitis were consecutively enrolled in this study. FMF patients with concurrent infectious diseases were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
1
9
1
1
Order By: Relevance
“…PCT is also known as an inflammation marker, and has been advocated as a useful test for differentiating abdominal FMF attacks from acute appendicitis. This suggestion is based on the observations that PCT levels tend to remain <0.5 ng/ mL during FMF abdominal attacks, but are elevated during acute appendicitis [29]. In our case, although the preoperative PCT level (0.65 ng/mL) was consistent with previous findings, the PCT level was much higher (1.32 ng/mL) at the time of the patient's first admission for an FMF abdominal attack.…”
Section: Discussionsupporting
confidence: 85%
“…PCT is also known as an inflammation marker, and has been advocated as a useful test for differentiating abdominal FMF attacks from acute appendicitis. This suggestion is based on the observations that PCT levels tend to remain <0.5 ng/ mL during FMF abdominal attacks, but are elevated during acute appendicitis [29]. In our case, although the preoperative PCT level (0.65 ng/mL) was consistent with previous findings, the PCT level was much higher (1.32 ng/mL) at the time of the patient's first admission for an FMF abdominal attack.…”
Section: Discussionsupporting
confidence: 85%
“…This is also reflected by the poor sensitivity of 0.14, which, from the authors' point of view, prohibits its usage as a potential diagnostic marker. As our first results contradicted those reported by Kisacik et al [14] , very early on in our study, we began analyzing the method of determining the levels of PCT and specimen collection to rule out systematic errors that may have led to lower PCT concentrations than those reported by other authors. In addition, since the PCT controls, who were all septic patients from the surgical ICU of our respective departments, were positive and evaluated identically, we concluded that the measurement of PCT was without error.…”
Section: Discussioncontrasting
confidence: 57%
“…Acute appendicitis in adolescents or adults has rarely been subject of research regarding the diagnostic value of PCT. The only study available to date that investigated adult patients is by Kisacik et al [14] , who studied 34 adult patients with acute appendicitis and 28 with familial Mediterranean fever attacks. They report PCT levels that are higher than 0.5 ng/ml in 62% of their patients with acute appendicitis and in 11% of their patients with familial Mediterranean fever.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the number of cases in this study was not large enough to allow the detection of differences in the frequency of attacks between these groups. FMF can cause severe abdominal pain that may lead to inappropriate surgical interventions 22,38 . We conclude that the homozygous genotype causes a predisposition to severe disease ( P < 0.01).…”
Section: Discussionmentioning
confidence: 70%